Exploring the transformative effects of the Rohingya settlement on secondary school students in Bangladesh - Shahidul Islam; Md. Rabbi Khan; Eva , Nawshin Farzana (Journal of Interdisciplinary Studies in Education, 2024)
In this study, we aimed to investigate the impact of the displaced Rohingya settlement on secondary school students in Cox’s Bazar, focusing on their perceptions and the challenges they encounter. All the secondary school students, teachers, parents, community leaders, and administrative persons of Cox’s Bazar district were the population of this study. Utilizing interviews and focus group discussions, data were gathered from thirty students, five teachers, five parents, five community leaders, the UNO, and the USEO of Cox’s Bazar. Thematic analysis revealed that the Rohingya settlement significantly affects students’ learning environments both at school and home, with economic, communication, security, and health-related challenges identified. Positive and negative economic impacts were noted, along with communication difficulties and security concerns. Additionally, students exhibited tendencies towards amoral behavior when interacting with Rohingya individuals, and health issues adversely affected their learning. Policy recommendations include the appointment of additional teachers by NGOs/INGOs to alleviate teacher shortages, the construction of sustainable cyclone shelters within Rohingya camps, and enhanced parental monitoring to safeguard students from insecurity and immoral activities.